China's military operations other than war - Hirono, Miwa; Xu, Manshu (Taylor & Francis (Routledge), 2013)
Although political friction and ideological differences between China and the West can hamper co-operation on missions known as ‘Military Operations Other than War’, the UK and China have achieved a certain level of success in this regard, particularly in relation to UN peacekeeping and counter-piracy operations. In this article, Miwa Hirono and Manshu Xu argue that the key has been to use multilateral platforms to frame bilateral collaboration, thereby diminishing Chinese perceptions of the associated political risks. Thus it is useful for Western militaries to exploit multilateralism to make military co-operation more attractive to China